BDE-209: kinetic studies and effect of humic substances on photodegradation in water - Leal, J. F.
BDE-209 is a brominated flame retardant and a priority contaminant, which has been found in several environmental matrices, namely, in water. To date, there are no quantum yield data for BDE-209 photodegradation by sunlight in water, to allow predicting half-life times in aquatic systems. In this work, the kinetics of BDE-209 photodegradation in water was studied and the influence of different fractions of aquatic humic substances (HS) was evaluated. Aqueous solutions of BDE-209 exposed for different periods of time to simulated sunlight were analyzed by HPLC-UV after being concentrated using dispersive liquid-liquid microextraction (DLLME) or solid-phase extraction (SPE). The photodegradation of BDE-209 in aqueous solution followed pseudo-first-order kinetics. The average quantum yield obtained of 0.010 ± 0.001 (about 20-fold lower than the quantum yield determined in ethanol) allow to predict an outdoor half-life time of 3.5 h. The photodegradation percentage of BDE-209 was not significantly affected by the XAD-4 fraction of HS, but it decreased substantially in the presence of humic and fulvic acids. Light screening by the humic substances could not explain this delay, which is probably the result of the association of the compound with the hydrophobic sites of the humic material.